Homo Administer and Sustainable Development: from Governance to the Ethics of Alterity (Research, Society and Development, 2022)
This article is a reflection on social vulnerabilities based on the concepts of work, poverty, inequalities and Law, as well as the social and political implications. The objective is to understand whether, in the perspective of the current socioeconomic and meritocratic structure, vulnerabilities are caused by wealth itself. Poverty in Brazil is also associated with the absence of ethical behavior allied to the limited concept of financial development. It also seeks to demonstrate that ethics plays a relevant conditioning role in the social development project. As for the design of the methodology, the research is exploratory bibliographic with a qualitative approach. In view of this, it is concluded that it is important to rethink the way of living and of disposing of productive resources, in addition to the importance of policies that make education a means of promoting alterity and autonomy that result in conscious, responsible and subsidiary attitudes.